Stakeholders’ Attitude in Implementing Cleaner Production: Case of The Pharmaceutical Industry in Jakarta - Alin Erlita Nurfatiha; Ahyahudin Sodri; Dwi Nowo Martono (Postgraduate, University of Mataram, 2023)
The medicines production process in the pharmaceutical industry, especially in herbal medicines, impacts natural resources and environmental pollution. Implementing cleaner production (CP) can be a profitable solution for companies. Stakeholders’ attitudes toward implementing CP are needed to achieve a sustainable pharmaceutical industry. This research was conducted at the Company X, a pharmaceutical industry that produces herbal medicines located in DKI Jakarta Province. This research aims to identify and analyze stakeholder attitudes toward CP as assessed based on knowledge, responses, and practices through a questionnaire. The sample was conducted on 122 stakeholders participating in production and environmental management activities, including the Manager, Supervisor, and Staff. The results show that all stakeholders’ knowledge, responses, and practices have a good average criteria. The most significant number of stakeholders who were respondents were production staff at 37.7%. From the results of this research, it is hoped that all respondents will know the herbal medicine production process and implement CP at Company X.